Microstructure and Mechanical Properties of 5A06 Aluminum Alloy with Variable Gas TIG Welding - QI Xin; DAI Hongbin (Journal of Harbin University of Science and Technology, 2021)
In order to study the microstructure and mechanical properties of 5A06 aluminum alloy with variable gas TIG welding, (Ar-Ar) variable gas TIG welding and traditional continuous gas TIG welding were used to carry out surface surfacing welding on 4mm thick 5A06 aluminum alloy plate. We observe the metallographic structure of the weld on the surface of the weld under air and variable air, and test the tensile strength of the 5A06 aluminum alloy butt-welded plate sample under 1Hz variable air.The results show that: the variable aeration has a stirring and impacting effect on the molten pool, and the penetration depth is significantly greater than that under the traditional aeration.Compared with the weld structure under the traditional aeration, the weld structure under the variable aeration has more precipitation phase, and the distribution of the strengthening phase is evenly dispersed, which increases the strength of the weld, thereby improving the quality of the weld. Compared with the base material, the plasticity of the 5A06 aluminum alloy butt-welded plate sample under variable aeration decreases, which is 95% of the base material′s tensile strength.The fracture location is at the weld, and the fracture form is ductile fracture.